Digital Transformation and Professional Conduct of Lawyers: Transformasi Digital dan Etika Profesi Advokat - Azmi, Li Ulil; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2025)
General Background: The modernization of Indonesia’s legal system has introduced digital processes such as e-court services, reshaping the professional landscape of lawyers. Specific Background: As legal practitioners, lawyers must navigate evolving regulations and technological tools while maintaining ethical integrity. Knowledge Gap: Despite rapid digital integration, limited studies explore how technology practically supports lawyers’ professionalism and legal responsibilities. Aims: This study examines how lawyers adopt and utilize technology to sustain professional conduct, efficiency, and public trust. Results: Findings reveal that technology simplifies case management, legal research, and communication through digital platforms, yet requires continuous adaptation and ethical awareness. Novelty: The study offers empirical insights into how technological competence aligns with ethical advocacy in Indonesia’s legal practice. Implications: Strengthening digital literacy and ethical discipline among lawyers is crucial for ensuring justice delivery and sustaining professionalism in the digital era. Highlights: Technology facilitates efficiency and transparency in legal practice. Ethical use of digital tools strengthens client trust and justice. Continuous learning ensures professional competence in a digitalized legal system. Keywords: Technology, E-Court, Legal Ethics, Lawyer Professionalism, Digital Transformation